Solvothermal synthesis and good microwave absorbing properties for magnetic porous-Fe3O4/graphene nanocomposites - Xiaojun Zeng; Bai Yang; Haozhe Yang; Lingyu Zhu; Ronghai Yu (AIP Advances, 2017)
The magnetic porous-Fe3O4/graphene nanocomposites have been fabricated by a facile solvothermal method. The porous Fe3O4 nanospheres are embedded uniformly in the graphene oxide (GO) sheets to form a 3D Fe3O4/GO nanocomposite network. The dielectric properties for the Fe3O4/GO composites can be greatly improved by the 7 wt% GO additions. Good impedance matching can be also obtained in these Fe3O4/GO composites, which is proved to dominate their excellent microwave absorbing properties including the minimum reflection loss (RL) value of -43.7 dB at 6.8 GHz with a sample thickness of 5 mm and a broad absorption bandwidth of 5.92 GHz (below -10 dB). These porous-Fe3O4/GO composites also exhibit the good structural stability and low density, which shows their great potential application in high-performance electromagnetic microwave-absorbing materials.